al-Ghazali's Ihya' and the ethics of the modern strategic management : a critical evaluation - Ridzuan Bin Masri (International Institute of Islamic Thought and Civilization, International Islamic University Malaysia, 2012)
This study looks at on how Islamic ethical values can be assimilated into modern strategic management with the purpose of overcoming the issues of moral or ethical issues. The work was primarily based on the elucidation of al-Ghazali in his magnum opus,Iḥya'ʻulum al-Din, especially in the second volume of his work that mainly explains the rules, procedures and ethics of business and trade activities. For the purpose of bridging between both Islam and modern knowledge of management, the framework of al-Ghazali's ethics and the framework of the strategic management process were established to provide the methodical guidelines for the organization of the whole thesis. This study also considered the Islamic and Western worldviews. The researcher also used the narrations approach in some parts which referred to the history of Prophet Muhammad (SAW), his companions and other prominent Muslim caliphs to illustrate certain pointsduring the glorious age of Islamic civilization. The framework of this study was divided into strategy formulation, strategy implementation and strategy evaluation. During the implementation of the whole strategic processes, the bridging of the Islamic approach of ethics was done in which, the wisdom (ḥikmah), courage (shaja'ah), temperance ('iffah) and justice (ʻadalah) were became the focal point of the work. This work did not completely discard the modern knowledge and theories of management. Certain criticisms were put forward to some of the theories of modern management which contravene with Islamic moral and ethical values. Simultaneously, the researcher also used some of the modern theories of management that were considered as not to contravene the principles of to Islam. , along with the Islamic approach of management.In some parts, few verses of the Quran and related Hadith were used to fortify the deliberation of some theories and propositions. Nevertheless, all Quranic verses and Hadiths used were similar to those of the Quranic verses and Hadiths depicted and used by al-Ghazali in the Iḥya'Ihya'. A careful re-examination of the Quranic verses and Hadith in the translation version of the Iḥya' and this thesis was also done to verify usage.